The application of Artificial Intelligence to Agriculture. Use of drones and Data Protection. (Justicia &Derecho, 2026)
This article focuses on the application of artificial intelligence in agriculture. It will analyze the use of drones in agriculture and the problems that arise in relation to fundamental rights and personal data.
Keywords: agriculture; drones; protection; data; artificial intelligence